Reciprocal Regulation of Mitofusin 2-Mediated Mitophagy and Mitochondrial Fusion by Different PINK1 Phosphorylation Events - Li, Jiajia; Dang, Xiawei; Franco, Antonietta; Dorn, Gerald W (Frontiers in Cell and Developmental Biology, 2022)
Mitochondrial repair is essential to metabolic homeostasis. Outer mitochondrial membrane mitofusin (MFN) proteins orchestrate mitochondrial fusion that opposes mitochondrial degeneration caused by senescence. Depending upon physiological context, MFN2 can either mediate mitochondrial fusion or recruit cytosolic Parkin to initiate mitophagic elimination. Because it is not clear how these events are counter-regulated we engineered and expressed MFN2 mutants that mimic phosphorylated or non-phosphorylatable MFN2 at its PINK1 phosphorylation sites: T111, S378 and S442. By interrogating mitochondrial fusion, polarization status and mitophagy as a function of inferred MFN2 phosphorylation status, we discovered that individual MFN2 phosphorylation events act as a biological “bar-code”, directing different mitochondrial fates based on phosphorylation site state. Experiments in Pink1 deficient cells supported a central role for PINK1 kinase as the pivotal regulator of MFN2. Contrary to popular wisdom that Parkin-mediated ubiquitination regulates MFN-mediated mitochondrial fusion, results in Prkn null cells demonstrated the dispensability of Parkin for MFN2 inactivtation. These data demonstrate that PINK1-mediated phosphorylation is necessary and sufficient, and that Parkin is expendable, to switch MFN2 from fusion protein to mitophagy effector.